Hard-magnetic phenomena enable autonomous self-healing elastomers - Garcia-Gonzalez, Daniel; Ter-Yesayants, Tigran; Moreno Mateos, Miguel Angel; Lopez-Donaire, Maria Luisa (Composites Part B-Engineering, 2023)
We propose a new concept of self-healing soft material that does not require external actuation to heal after rupture. This consists of a sticky and soft elastomeric matrix filled with hard-magnetic particles. When the material breaks into two or more parts and these are approached to each other, the magnetic particles with residual magnetisation interact closing the crack. Then, if new mechanical loading is applied, the composite acts as a continuum structure transmitting internal forces homogeneously until reaching a new failure strain threshold. We demonstrate this novel concept with experiments under tensile loading and with a magneto-mechanical constitutive model that explains the healing mechanisms. The results indicate that the proposed soft materials are able to, after several fracture cycles, sustain mechanical loading beyond 20 % strains without compromising the structural integrity. The healed material experiences no mechanical degradation during cyclic loading and healing cycles. Moreover, on its healed state, it can sustain higher stresses than the original material without residual magnetisation. We demonstrate that the strain at failure is determined by the combined effect of magnetic and adhesive contributions, which are modulated by the applied deformation rate. Furthermore, we reveal that the combination of soft and hard magnetic particles in a hybrid magnetorheological elastomer enables superior healing performance.
Created from Fastlane, Scopus look-up
Keywords: Magneto-mechanics; Magnetorheological elastomers (MREs); Multifunctional materials; Self-healing; Soft robotics